Potential determinants of vitamin D in Finnish adults: a cross-sectional study from the Northern Finland birth cohort 1966 - Palaniswamy, Saranya; Hypponen, E; Williams, Dylan; Jokelainen, Jari; Lowry, Estelle; Keinanen-kiukaanniemi, Sirkka; Herzig, Karl-Heinz; Jarvelin, Marjo-Riitta; Sebert, Sylvain (BMJ Open, 2017)
Objective Evidence from randomised controlled trials suggests that vitamin D may reduce multimorbidity, but very few studies have investigated specific determinants of vitamin D2 and D3 (two isoforms of 25-hydroxyvitamin D). The aim of the study was to investigate the determinants of vitamin D2 and D3 and to identify the risk factors associated with hypovitaminosis D. Design Cross-sectional study. Setting Northern Finland Birth Cohort 1966. Participants 2374 male and 2384 female participants with data on serum 25(OH)D2 and 25(OH)D3 concentrations measured at 31 years of age (1997), together with comprehensive measures of daylight, anthropometric, social, lifestyle and contraceptive cofactors. Methods We assessed a wide range of potential determinants prior to a nationwide fortification programme introduced in Finland. The determinants of 25(OH)D2, 25(OH)D3 and 25(OH)D concentrations were analysed by linear regression and risk factors for being in lower tertile of 25(OH)D concentration by ordinal logistic regression. Results At the time of sampling, 72% of the participants were vitamin D sufficient (≥50 nmol/L). Low sunlight exposure period (vs high) was associated positively with 25(OH)D2 and negatively with 25(OH)D3 concentrations. Use of oral contraceptives (vs non-users) was associated with an increase of 0.17 nmol/L (95% CI 0.08 to 0.27) and 0.48 nmol/L (95% CI 0.41 to 0.56) in 25(OH)D2 and 25(OH)D3 concentrations. Sex, season, latitude, alcohol consumption and physical activity were the factors most strongly associated with 25(OH)D concentration. Risk factors for low vitamin D status were low sunlight exposure defined by time of sampling, residing in northern latitudes, obesity, higher waist circumference, low physical activity and unhealthy diet. Conclusions We demonstrate some differential associations of environmental and lifestyle factors with 25(OH)D2 and 25(OH)D3 raising important questions related to personalised healthcare. Future strategies could implement lifestyle modification and supplementation ...